Antioxidant Screening and Sunscreen Activity of Nanocream of Purified Extract of Kenikir Leaves (ETDK) and Tampoi Fruit Peel Extract (EKBT): Skrining Antioksidan dan Aktivitas Tabirsurya Nanokrim Ekstrak Terpurifikasi Daun Kenikir (ETDK) dan Ekstrak Kulit Buah Tampoi (EKBT) - Rahman, Ika Ristia; Kartikasari, Dian; Kurnianto, Erwan; Herdaningsih, Sulastri (Universitas Tadulako, 2021)
Background: UV lights are free radicals that can cause damage to the skin, such as redness, burning, pigmentation, and even cancer. Kenikir leaf purified extract (ETDK) and Tampoi fruit peel extract (EKBT) contain flavonoid compounds. Flavonoid compounds can be antioxidants and sunscreens due to the presence of chromophore groups that can absorb UV rays to reduce exposure to the skin. Objectives: This study aims to determine the antioxidant activity and the ability of sunscreen nano cream Purified extract of Kenikir leaves and Tampoi fruit peel extract. Material and metode: Nanocream is made with 3 ETDTK-EKBT combination formulas, II ETDK formulas, III EKBT formulas. The antioxidant activity test was carried out using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method and the sunscreen activity test using the UV-Vis spectrophotometric method to calculate the SPF value of the preparation (Mansur's method). Result: The results showed that the nano cream formula had a strong antioxidant activity with the per cent inhibition of formula I 78.28%, formula II 68.49%, and formula III 73.00%. The activity test results as a sunscreen formulation of purified extract nano cream from Kenikir leaves and nano cream from Tampoi fruit peel extract had extra protection ability with a sun-protecting factor value of 7 while the nano cream formula combined extract with an SPF value of 10 gave the maximum protection category. Conclusion: nano cream have potential as antioxidants and sunscreens.